2013
DOI: 10.1016/j.colsurfa.2013.04.046
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of spreading drops

Abstract: OATAO is an open access repository that collects the work of Toulouse researchers and makes it freely available over the web where possible. This is an author-deposited version published in : http://oatao.univ-toulouse.fr/ Eprints ID : 10539Any correspondance concerning this service should be sent to the repository administrator: staff-oatao@listes-diff.inp-toulouse.fr g r a p h i c a l a b s t r a c t• Numerial simulation of spreading drops on a wettable surface.• We discuss the effect of the main parameters … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(26 citation statements)
references
References 25 publications
0
25
1
Order By: Relevance
“…This is consistent with theoretical predictions [9,11] and experimental results [8,9,11,12,17] from literature. Recently, Legendre and Maglio numerically calculated that if the early wetting was dominated by viscous dissipation, the spreading should follow a power law with α = 2/3 [38]. However, in our experiments we found that the maximum α for all liquids was 0.5 and that α was only dependent on θ eq .…”
Section: A Inertial Wettingcontrasting
confidence: 60%
“…This is consistent with theoretical predictions [9,11] and experimental results [8,9,11,12,17] from literature. Recently, Legendre and Maglio numerically calculated that if the early wetting was dominated by viscous dissipation, the spreading should follow a power law with α = 2/3 [38]. However, in our experiments we found that the maximum α for all liquids was 0.5 and that α was only dependent on θ eq .…”
Section: A Inertial Wettingcontrasting
confidence: 60%
“…As a consequence, a sub-grid model as described in Dupont and Legendre [10] has to be introduced in order to make possible macroscopic simulations. Based on this approach, the modeling developed in recent works [23,21,17] appears to be the more -the wall condition seen by the fluid is a non slip condition, -the interface shape is connected by a dynamic relation to the characteristics of the contact line at the nanoscale.…”
Section: Discussionmentioning
confidence: 99%
“…The main difference with experiments is due to the oscillations observed at the end of the drop spreading. Such oscillations are induced by the propagation of capillary wave resulting in some cases of a droplet ejection [26,23]. In the simulations, the top of the drop is free to Table 5 Grid used in the simulations reported in Section 5. move and oscillate due to the capillary waves while in the experiments the drop remains pinned to the needle used for the deposit.…”
Section: Spreading Dropmentioning
confidence: 99%
“…The second method used adopts a volume-of-fluid (VOF) approach. 15,16 In the version of the VOF method employed in the present study, there is no interface reconstruction but the interface is limited to 2 to 3 grid cells, thanks to an accurate flux-corrected transport algorithm. The shear stress singularity at the wall is removed by using the Navier slip boundary condition.…”
mentioning
confidence: 99%